The Nurse in Popular Media Critical Essays - Harmes, Marcus; Harmes, Barbara; Harmes, Meredith A. (McFarland, 2021)
The image of the nurse is ubiquitous, both in life and in popular media. One of the earliest instances of nursing and media intersecting is the Edison phonographic recording of Florence Nightingale's voice in 1890. Since then, a parade of nurses, good, bad or otherwise, has appeared on both cinema and television screens. How do we interpret the many different types of nurses- real and fictional, lifelike and distorted, sexual and forbidding-who are so visible in the public consciousness? This book is a comprehensive collection of unique insights from scholars across the Western world. Essays explore a diversity of nursing types that traverse popular characterizations of nurses from various time periods. The shifting roles of nurses are explored across media, including picture postcards, film, television, journalism and the collection and preservation of uniforms and memorabilia.